Rat ventral prostate microsomal biotransformation of ethanol to acetaldehyde and 1-hydroxyethyl radicals: Its potential contribution to prostate tumor promotion - Castro, Gerardo Daniel (2002)
Rat ventral prostate microsomal fraction was able to biotransform ethanol to acetaldehyde and 1-hydroxyethyl radicals (1HEt) in the presence of NADPH and oxygen. The enzymatic processes involved were not inhibited by desferrioxamine, CO, SKF 525A, 4-methylpyrazole, or polyclonal antibody against P450 reductase but they were significantly inhibited by diethyldithiocarbamate, 2-mercapto-1-methylimidazol, thiobenzamide, or diphenyleneiodonium chloride. Results would suggest the partial participation in these ethanol bioactivation processes of flavin containing monooxygenase (FMO) and/or other flavin dependent oxidases/ peroxidases and of a non-iron metal-containing enzymes. Acetaldehyde and free radicals production by prostate microsomal fraction might potentially contribute to tumor promotion in heavy alcohol drinkers.